Fate of titanium in alkaline electro-reduction of sintered titanomagnetite. (9th October 2020) - Bjareborn, Oscar; Arif, Tanzeel; Monaghan, Brian; Bumby, Chris W
Abstract: Direct electrochemical reduction of iron ore in concentrated NaOH electrolyte has been proposed as a potential route to substantially reducing the global steel industry's CO2 emissions. Here, we report the solid-state electro-reduction of sintered pellets formed from titanomagnetite ironsand. This commercial iron ore contains ∼4 wt.% Ti which is directly incorporated within the magnetite lattice. At 110 °C, these pellets are electrochemically reduced and exhibit a well-defined reaction front which moves into the pellet as the reaction progresses. The electro-reduction process selectively produces iron metal, whilst the Ti content is not reduced. Instead, Ti becomes enriched in segregated oxide inclusions, which are subsequently transformed to a sodium iron titanate phase through taking up Na + from the electrolyte. These inclusions adopt an elongated shape and appear to exhibit locally preferential alignment. This suggests that they may nucleate from the microscopic titanohematite lamellae which naturally occur within the original ironsand particles. The expulsion of contaminant Ti-oxides from the final reduced metal matrix has implications for the potential to development of an industrial electrochemical iron-making process utilising titanomagnetite ore.